Pengaruh Program Literasi Terhadap Prestasi Belajar Siswa Kelas III SDN 244 Inpres Bera Kabupaten Tana Toraja - Irene Hendrika Ramopoly; Hasriani Zainuddin (LPPM UKI Toraja, 2021)
Literacy program is a reading activity 15 minutes before the study time begins. Literacy programs teach students the ability to independently access, understand, and use things intelligently through reading, writing, seeing, listening, and speaking activities that can be realized in life. This research aims to find out